Contributions to the morphology and histology of the reproductive system of Cratena capensis Barnard (Opisthobranchiata: Nudibranchiata) - Du Preez, Benjamin (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1990.